2006
DOI: 10.1029/2006gl028115
|View full text |Cite
|
Sign up to set email alerts
|

Production of odd hydrogen in the mesosphere during the January 2005 solar proton event

Abstract: [1] Using measurements from the MLS/Aura and GOMOS/Envisat instruments together with a 1-D ion and neutral chemistry model we study the changes in odd hydrogen and ozone in the mesosphere during the January 2005 solar proton event. The unique observational data allow us for the first time to directly test the HO x production theory which involves complex ion chemistry. MLS measurements from the northern polar region show increases of OH concentrations by over 100% around the stratopause, and by up to one order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 13 publications
(17 reference statements)
7
113
0
Order By: Relevance
“…Damiani et al: SEP effects on Polar Atmosphere rise of HO x during the solar particle flux hitting the Earth's atmosphere on 17 and 20 January. Verronen et al (2006) demonstrated that the OH rise (measured by the MLS EOS instrument on the AURA satellite) and the ozone depletion (measured by the Gomos instrument on the Envisat satellite) were in good agreement with model expectations for 18 and 20 January at 69 • -70 • N at twilight condition. Moreover, Damiani et al (2007) 1 highlights that the OH rise, averaged at 82 • N and 0.1 hPa (∼64 km) with the same solar zenith angle (SZA ∼108 • /LST: 7.67 h, to avoid daily variability), increased by hundreds of percent on 18 January (less on 20 January), although the same violent rise did not appear in the equivalent location of the Southern Hemisphere.…”
Section: Introductionsupporting
confidence: 62%
“…Damiani et al: SEP effects on Polar Atmosphere rise of HO x during the solar particle flux hitting the Earth's atmosphere on 17 and 20 January. Verronen et al (2006) demonstrated that the OH rise (measured by the MLS EOS instrument on the AURA satellite) and the ozone depletion (measured by the Gomos instrument on the Envisat satellite) were in good agreement with model expectations for 18 and 20 January at 69 • -70 • N at twilight condition. Moreover, Damiani et al (2007) 1 highlights that the OH rise, averaged at 82 • N and 0.1 hPa (∼64 km) with the same solar zenith angle (SZA ∼108 • /LST: 7.67 h, to avoid daily variability), increased by hundreds of percent on 18 January (less on 20 January), although the same violent rise did not appear in the equivalent location of the Southern Hemisphere.…”
Section: Introductionsupporting
confidence: 62%
“…Observations of HOCl enhancements in response to the solar proton event gave evidence of perturbed chlorine chemistry as well as the first experimental evidence of perturbed HO x chemistry . These HO x perturbations were later confirmed by direct hydroxyl observations (Verronen et al, 2006). Within the context of this climatological analysis it is important to note that HOCl measurements in October and November 2003 might not be representative for this season, although the observed HOCl enhancements were very localized and lasted only a few days and thus are not resolved in the monthly zonal means.…”
Section: The Halloween Solar Storm In 2003mentioning
confidence: 81%
“…Below 40 km, a(z) is taken to have a constant value of two. This assumption is a limitation since work with a detailed ion chemistry model (Verronen et al, 2006) indicates that HNO 3 is an important direct product through ion-ion recombination reactions with secondary OH production via photodissociation. As noted by Verronen et al (2006) assuming a constant HO x production leads to an underestimation of HO x during sunrise and sunset which also affects ozone loss, but only lasts for a short period outside polar regions.…”
Section: Epp Parameterizationmentioning
confidence: 99%
“…This assumption is a limitation since work with a detailed ion chemistry model (Verronen et al, 2006) indicates that HNO 3 is an important direct product through ion-ion recombination reactions with secondary OH production via photodissociation. As noted by Verronen et al (2006) assuming a constant HO x production leads to an underestimation of HO x during sunrise and sunset which also affects ozone loss, but only lasts for a short period outside polar regions. Figure 2 shows the time series of the ion pair production rate for the three types of EPP used in the model along with the F10.7 solar variability index (adjusted Penticton/Ottawa 2800 MHz solar flux, http://www.ngdc.noaa.gov/ stp/solar/flux.html).…”
Section: Epp Parameterizationmentioning
confidence: 99%